Green Islam: New-Theology and Implementation of Pesantren Al Qodir Managerial System - Reza Bakhtiar Ramadhan; Aris Risdiana (Dialogia: Islamic Studies and Social Journal, 2021)
This paper studied the concept of Green Islam as a new-theology spreads at Pesantren al-Qodir, Sleman Yogyakarta. The theology has a series of ideas on nation-state, Islāmic studies, and interpretation of Islamic teachings on ecological issues. In implementing that theology, Pesantren al-Qodir arranged many programs such as preventing socio-ecological crisis resulting from uncaring human attitudes on the ecosystem. These uncaring ones encourage al-Qodir to cooperate with many partners and promote that theology. Training of Trainer (ToT) for Volunteer for Natural Disasters is just a sample of how al-Qodir implements its program. For Green Islam Theology, ecological studies are then philosophically not secular but religion. It is needed as a crucial tool for continuing the life of a human being. K.H Masrur Ahmad as a leader of al-Qodir has cooperated with and invited all his partners not only to focus on aspects of life in the hereafter but also on the best pragmatic interests. The most important thing in the view of Green Islam Theology is how to erase ecological crisis resulted from bad uncaring human actions. It is an implementation of the theories of developmental ecology proposed by Bronfenbrenner. He said that human development is influenced by society and environmental habitation.